2019
DOI: 10.1088/1755-1315/292/1/012047
|View full text |Cite
|
Sign up to set email alerts
|

Food Safety in the Protection of the Right to Health

Abstract: Food safety is still not getting the attention it should; therefore the condition of food safety in Indonesia is still a concern. WHO reports that around 2 million of the world’s population die every year due to unsafe food. In Indonesia, Indonesia Agency of Drug and Food Control (BPOM) reported that the outbreak of food poisoning caused the death of 2500 people and as many as 411,500 people sick each year. Food safety is a right for the community but has not been accomplished until now. The study aimed to des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…(43) Dietary iron can be safe-guarded as protection of the right to health. (44) Several recommended research topics associated with iron deficiency anemia are the topics of clinician, pathogenesis, and biofortification. These 3 topics have high chances for inclusion in research associated with iron deficiency anemia, because this research has found its path, and many topics have been considered.…”
Section: Discussionmentioning
confidence: 99%
“…(43) Dietary iron can be safe-guarded as protection of the right to health. (44) Several recommended research topics associated with iron deficiency anemia are the topics of clinician, pathogenesis, and biofortification. These 3 topics have high chances for inclusion in research associated with iron deficiency anemia, because this research has found its path, and many topics have been considered.…”
Section: Discussionmentioning
confidence: 99%
“…The Indonesian constitution states that is responsible, and must actively provide health service to citizens in accordance with the values of Pancasila (Arifat, 2018) Law Number 18 of 2012 on Food Mandates that food is the most important basic human need, and its fulfillment is part of human rights guaranteed in the 1945 Constitution. According research by Damayanti et al, (2019) the number of poisoning cases that occur in Indonesia shows that food safety conditions in Indonesia are of lower quality. Protection of the right to health as stated in Health Law Number 36 of 2009 hasn't been implemented properly, one of the causes is that there are still many dangerous food products circulating in the market so that there needs to be attention from stakeholders in protecting the right to public health.…”
Section: Discussionmentioning
confidence: 99%
“…According to Haryadi in Damayanti et al, (2019) reported that the Agency of Drug and Food Control Republic of Indonesia stated that the food poisoning outbreaks cause the death of 2.500 people and sicken as many as 411.500 people each year. Food safety is a right for the community society but hasn't been achieved until now.…”
Section: Discussionmentioning
confidence: 99%
“…Non-essential metal (As, Cd, Li, Ni, Pb, Ti) are metals whose benefits are unknown and when absorbed in body can be toxic [8]. Food safety level is an effort needed in preventing food contamination from chemical, biological, and other object that are harmful to human health [9]. Each country can establish maximum limit standard of food product contamination to protect the community.…”
Section: Introductionmentioning
confidence: 99%